Gene Expression Deficits in a Subclass of GABA Neurons in the Prefrontal Cortex of Subjects with Schizophrenia - Hashimoto, Takanori; Volk, David W; Eggan, Stephen M; Mirnics, Karoly; Pierri, Joseph N; Sun, Zhuoxin; Sampson, Allan R; Lewis, David A (The Journal of neuroscience, 2003)
Markers of inhibitory neurotransmission are altered in the prefrontal cortex (PFC) of subjects with schizophrenia, and several lines of evidence suggest that these alterations may be most prominent in the subset of GABA-containing neurons that express the calcium-binding protein, parvalbumin (PV). To test this hypothesis, we evaluated the expression of mRNAs for PV, another calcium-binding protein, calretinin (CR), and glutamic acid decarboxylase (GAD 67 ) in postmortem brain specimens from 15 pairs of subjects with schizophrenia and matched control subjects using single- and dual-label in situ hybridization. Signal intensity for PV mRNA expression in PFC area 9 was significantly decreased in the subjects with schizophrenia, predominately in layers III and IV. Analysis at the cellular level revealed that this decrease was attributable principally to a reduction in PV mRNA expression per neuron rather than by a decreased density of PV mRNA-positive neurons. In contrast, the same measures of CR mRNA expression were not altered in schizophrenia. These findings were confirmed by findings from cDNA microarray studies using different probes. Across the subjects with schizophrenia, the decrease in neuronal PV mRNA expression was highly associated ( r = 0.84) with the decrease in the density of neurons containing detectable levels of GAD 67 mRNA. Furthermore, simultaneous detection of PV and GAD 67 mRNAs revealed that in subjects with schizophrenia only 55% of PV mRNA-positive neurons had detectable levels of GAD 67 mRNA. Given the critical role that PV-containing GABA neurons appear to play in regulating the cognitive functions mediated by the PFC, the selective alterations in gene expression in these neurons may contribute to the cognitive deficits characteristic of schizophrenia.